A Vitual Reality Digital Comic: Fostering Environmental Literacy through Baduy Local Wisdom - Khoirunnisa, Khoirunnisa; Sudarmin, Sudarmin; Priatmoko, Sigit; Nurhayati, Nunung (Unnes Science Education Journal, 2025)
The objectives of this study are developing and evaluating the effectiveness of a digital comic based green chemistry instructional materials integrated with Virtual Reality (VR) and Baduy local wisdom to improve students’ sustainable environmental literacy. Utilizing Research and Development (R&D) method using 4D model, all instructional components (VR digital comic, teaching module, test instruments, and questionnaires) were validated by experts and deemed highly valid (Aiken’s V > 0.80). A try out of the VR digital comic media with small scale revealed enggaging category with an average percentage exceeding 90%. The Independent Sample t-Test in the experimental and control classes showed a statistically significant difference in posttest scores (Sig. <.001), proving a substantial increase in learning outcomes in the experimental class. Environmental literacy analysis based on the National Environmental Literacy Assessment (NELA) indicators supports these findings: the experimental group achieved a high-level criterion (score: 190) compared to the control group (score: 169). The most prominent improvement in the experimental class was observed in the knowledge and cognitive skills dimensions. The implementation of this learning innovation effectively improves students’ environmental literacy, particularly in knowledge and cognitive skills. Nevertheless, the development of deeply internalized environmental attitudes and behaviors may require more time and a more in-depth approach. However, but this innovation shows significant potential in shaping a generation responsible for environmental issues.